Pengaruh Pinjaman Dana KUR Terhadap Peningkatan Usaha Mikro Kecil Menengah di Dsa Waiboga Kecamatan Sulabesi Tengah. - Muhaidin Masuku (Jurnal Ilmiah Wahana Pendidikan, 2026)
Not all members of the middle-income community possess sufficient capital to start or expand their businesses; consequently, they require financial assistance in the form of loans or credit—such as the KUR (People's Business Credit) program offered by banking institutions. The research problem addressed here is whether KUR loans influence the growth of Micro, Small, and Medium Enterprises in Waiboga Village. The study aims to determine the impact of KUR loans on the growth of in Waiboga Village. This study employs a quantitative methodology, utilizing observation, questionnaires, and documentation for data collection. A full population study was conducted, as the total population size was fewer than 100 individuals. Simple regression analysis was used for data analysis, facilitated by SPSS Version 26 software. The simple regression results presented in Table 4.14 indicate that the KUR loan variable (Variable X) yielded a calculated t-value (t-count) of 2.200, which exceeds the critical t-value (t-table). Based on a significance level of 0.05 and degrees of freedom (df) calculated as df = n - k (or df = 63 - 2 = 61), the t-table value is 1.656. Furthermore, the significance value of 0.030 is less than 0.05. Since the calculated t-value exceeds the t-table value, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. Thus, the hypothesis. That KUR loans influence growth is supported by the research findings